Learning Spatial Aversion Is Sensory-Specific in the Hematophagous Insect Rhodnius prolixus - Minoli, Sebastian; Cano, Agustina; Pontes, Gina; Magallanes, Amorina; Roldán, Nahuel; Barrozo, Romina B. (Frontiers in Psychology, 2018)
Even though innate behaviors are essential for assuring quick responses to expected stimuli, experience-dependent behavioral plasticity confers an advantage when unexpected conditions arise. As being rigidly responsive to too many stimuli can be biologically expensive, adapting preferences to time-dependent relevant environmental conditions provide a cheaper and wider behavioral reactivity. According to their specific life habits, animals prioritize different sensory modalities to maximize environment exploitation. Besides, when mediating learning processes, the salience of a stimulus usually plays a relevant role in determining the intensity of an association. Then, sensory prioritization might reflect an heterogeneity in the cognitive abilities of an individual. Here, we analyze in the kissing bug Rhodnius prolixus if stimuli from different sensory modalities generate different cognitive capacities under an operant aversive paradigm. In a 2-choice walking arena, by registering the spatial distribution of insects over an experimental arena, we evaluated firstly the innate responses of bugs confronted to mechanical (rough substrate), visual (green light), thermal (32 ºC heated plate), hygric (humidified substrate), gustatory (sodium chloride) and olfactory (isobutyric acid) stimuli. In further experimental series bugs were submitted to an aversive operant conditioning by pairing each stimulus with a negative reinforcement. Subsequent tests allowed us to analyze if the innate behaviors were modulated by such previous aversive experience. In our experimental setup mechanical and visual stimuli were neutral, the thermal cue was attractive, and the hygric, gustatory and olfactory ones were innately aversive. After the aversive conditioning, responses to the mechanical, the visual, the hygric and the gustatory stimuli were modulated while responses to the thermal and the olfactory stimuli remained rigid. We present evidences that the spatial learning capacities of R. prolixus are dependent on the sensory modality of the conditioned stimulus, regardless their innate valence (i.e. neutral, attractive or aversive). These differences might be given by the biological relevance of the stimuli and/or by evolutionary aspects of the life traits of this hematophagous insect.